The unexpected everything - Matson, Morgan (Simon & Schuster BFYR, 2016)
"Seventeen year old Andie always has a plan, but when her father suffers a political scandal, her summer med school program is taken away from her, and a new guy comes into the picture, she finds a lot of unexpected things can happen when you're busy making other plans"...